Current minimization of the non-ideal voltage source with periodically time-varrying parameters by means of an active compensator - Siwczyński, Maciej; Pasko, Marian; Kłosiński, Radosław (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the problem of matching a receiver to the real voltage source is solved for the first time. The active current has been correctly determined in the real source with an inner parametric impedance and a parametric receiver. It has also been shown that a compensatory circuit should be selected from a larger class of two-terminal networks with changeable parameters.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka